Anti-tumor potential of Harmine and its derivatives: recent trends and advancements - Hemant Joshi; Sakshi Bhushan; Tanisha Dimri; Deepak Sharma; Katrin Sak; Abhishek Chauhan; Ritu Chauhan; Shafiul Haque; Faraz Ahmad; Manoj Kumar; Hardeep Singh Tuli; Damandeep Kaur (Discover Oncology)
Abstract Harmine is a β-carboline alkaloid derived from Peganum harmala, showing a solid antitumor potential in different types of human cancer cells. Unfortunately, the clinical application of this natural alkaloid has been impeded till now by severe toxic side effects, especially neurotoxicity, besides its poor water solubility. Therefore, over the recent years, several semisynthetic derivatives of harmine have been prepared and studied concerning their abilities to inhibit tumor cell proliferation, survival, angiogenesis, migration, and invasion in diverse preclinical models. This review article summarizes the anticancer effects of harmine and its synthetic derivatives, demonstrating their high potential to be developed as novel anticancer drugs to supplement our current therapeutic arsenal in the fight against the globally increasing rate of malignant disorders.